Strike on fiscal reform in Costa Rica - Mora Solano, Sindy (2022)
In 2019, thanks to the motivation of Dr. Ciska Raventós Vorst, a retired professor from the University of Costa Rica, a group of people interested in the study of protest and movementsas well as participants in the strike against the Fiscal Plan of the year 2018, we began to talk about this political event. With the conviction that the strike against the Fiscal Plan, whichdeveloped at the beginning of the administration of Carlos Alvarado Quesada (2018-2022), is one of the political phenomena that condense the fractures of today's Costa Rica, the proposal arose to prepare a series of reflections with the aim of offering them to those who are interested in the strike.